The Proofs Of Ebenezer Scrooges's Christian Joy In Charles Dickens’ A Christmas Carol (1843) - Epifanius Karso Seda Gadi; Cahyaningsih Pujimahanani; Haryono (Menulis: Jurnal Penelitian Nusantara, 2026)
The author of this article takes the title The Proofs Of Ebenezer Scrooge's Christian Joy in Charles Dickens' A Christmas Carol (1843).This article is about proofs of Christian Joy which found in Charles Dickens as one of main characters in the novella A Christmas Carol by Charles Dickens. The purpose of writing this article is to show proofs of the Christian joy of Christianity felt by Ebenezer Scrooge in the novella A Christmas Carol. The research method used in this study is descriptive qualitative. The topic of Christian Joy is chosen because it is important to find out the proofs of Christian Joy to Ebenezer Scrooge so that the readers can learn good lesson about how to understand about Christian Joy behaviour in life. In the modern era recently, most people will only concern about their mental health issue with all its gloom and joylessness.